(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Extensive work is being carried out in our country to integrate people with hearing impairments. One of the priorities of this field is to restore hearing ability by cochlear implantation in children with hearing impairment. On the basis of the state program on restoration of hearing in children with hearing impairment by installing cochlear implants in the country, the state provides free implants for children under 5 years of age. Extensive work is also underway on their pre- and post-cochlear implantation rehabilitation.